Does corporate governance influence leverage structure in Bangladesh? - Mohammad Nazim Uddin; Mohammed Shamim Uddin Khan; Mosharrof Hosen (International Journal of Financial Studies, 2019)
This paper examines the regulation of corporate governance on leverage structure decision-making in Bangladesh from 2003 to 2017. Appropriate panel methods are employed to control the problems of serial correlation, heteroskedasticity, and the cross-sectional nature of manufacturing companies. The study finds that corporate governance attributes such as board size, managerial ownership, and duality are the dominant factors for leverage decision-making. The results also indicate that control variables such as firm size and profitability have an influential role on leverage decision-making in Bangladesh. Our findings substantiate the idea that political and family connections to corporate governance structure greatly influence the leverage decision-making of corporate firms in Bangladesh.
Keywords: C22; C51; L16; 330; Bangladesh; board size; duality; leverage structure; managerial ownership